Antibiotic resistant microencapsulated probiotics synergistically preserved orange juice. Issue 1 (December 2016) - Hossain, Md; Al-Bari, Md; Mahmud, Zahid; Wahed, Mir
Abstract Background In contemporary medicine, the utilization of various dosage forms of probiotics is increasing both for the treatment of human and animal diseases in Bangladesh. A number of imported pharmaceutical probiotic preparations are available in the local markets at present without justification the scientific information of viability. This study was, therefore, designed to explore the viability of commercial probiotics as well as recommend the consumers for the better products in term of viability. Since probiotics preserved foods have expanded in acceptance, popularity and compliance, the goal of this research was also to investigate the combination effects of lactic acid bacteria (LAB) on development of functional foods like orange juice (OJ). Methods Here, we screened five commercially available pharmaceutical probiotic products for rejuvenation and identification of LAB and associated resistance against different classes of antibiotics. Finally, the isolated LAB were microencapsulated and compared with free form of bacteria for biopreservation of OJ. Results We observed an inconsistency between the feasible live LAB counts and the declaration of the manufacturing companies. The recovered viable bacteria of pharmaceutical probiotic preparations ranged between (6.2 -7.3) × 1010 at 37 °C and (5.33-7.1) × 1010 at 25 °C, the claimed (9-10) × 1010 colony forming unit (CFU)/g. The encapsulatedLactobacillus acidophilus (LAB 1), L. bulgaricus (LAB 2), Lactococcus lactis (LAB 3) andBifidobacterium bifidum (LAB 4) in OJ was resistant to drop out their viability as quickly as the free-form probiotic bacteria and >106 CFU/mL were still appeared after 6 wks of storage. Unencapsulated probiotics was found to have a significant reduction in viability in OJ at both 37 °C and 4 °C temperatures. However, the microencapsulation process significantly reduced the loss of viability of four probiotic bacteria as well as the control of acidification of OJ at 4 °C. Conclusions The loss of potency and spoiled food associated with pathogenic microbial growth are serious problems in tropical countries including Bangladesh. The biopreserved OJ will become an important functional food due to its expansion of shelf-time, market reputation, profits and innate tastes. This report has an indication that the combination of these four LAB may become good candidate for the development of an OJ with functional characteristics.